Effects of formulated Nigerian yellow maize, soybean, and crayfish blends on some growth performance and physiological status - Adegbusi, Halid Sheriff; Ismail, Amin; Mohd. Esa, Norhaizan; Mat Daud, Zulfitri Azuan (Springer Science and Business Media LLC, 2023)
In order to develop adequate complementary foods (CFs) to improve infant and young child feeding, the inclusion of animal source foods (ASFs) into plant-based foods (PBFs) is paramount. Unfortunately, the incorporation of ASFs into PBFs to formulate adequate CFs was infrequent in the developing countries, especially Nigeria. Yet, few CFs that were formulated by this strategy lacked adequate studies. This study investigated the compositional quality of CFs formulated from Nigerian yellow maize flour (MF), yellow maize + soybean flour (MSF), yellow maize + soybean + crayfish flour (MSCF), and commercial fortified wheat milk flour (FWMF) and their impact on the growth performance and physiological status of Sprague Dawley rats (SDRs). Compositional quality of CFs and their effects on the health status of SDRs were assessed. MSCF had higher protein and ash contents, its sulphur amino acids content was about 132% higher than that of MSF and astaxanthin was detected only in it. Determined antinutrients much reduced in MSCF compared with other CFs. The body weight gain (23.75 g) in yellow maize + soybean + crayfish diet (MSCD) group was significantly higher than other diet groups, whilst the value of protein efficiency ratio (2.59), feed efficiency ratio (0.30) in MSCD group was nominally higher compared with other groups. Better improvement in some of the biochemical and haematological parameters were observed in MSCD group compared with other groups, but no signs of illness, infection, and organ damage were seen in all the groups. The current study proved that crayfish could be used in a dietary modification to produce an adequate CF that potentiates improved growth performance and positive health outcomes in animals.